Kreativitas Guru Pendidikan Agama Islam dalam Pemanfaatan Media Pembelajaran dan Kemampuan Siswa dalam Memahami Materi PAI di Sekolah Dasar - Farida Iriani (DAYAH: Journal of Islamic Education, 2019)
This thesis research is motivated to create a learning atmosphere and learning process so that learners actively develop their potential to have the spiritual power of religion, personality, intelligence, noble character, and skill that needed him/her. Learning media as a vehicle for channeling or learning message container has a very important role in the teaching and learning process. In addition to attracting the attention of students, the media can also convey a message that is able to approach the actual object so that teachers do not need to explain elaborately about something that can not be displayed directly or concretely. The purpose of this research is to know the utilization of multimedia in improving the mastery of the material and How the results of multimedia implementation in improving the mastery of Islamic Religious Education (PAI) material in public elementary school Lambaro Angan. This test is useful for writers to add insight and experience in particular to improve the quality of teaching. For SD Negeri Lambaro Angan as a contribution of thought and for teachers to increase knowledge in the teaching and learning process. This research used the observation method. Interviews and documentation. This observation researchers use to dig the data, observe or pay attention to some things namely; the state educational institutions of Lambaro Angan State Element in the form of buildings, environmental situation, educators and teaching and learning process took place. Interview method researchers used to collect data on the use of instructional media and the results of multimedia implementation in increasing mastery of Islamic Religious Education (PAI). The data sources in this data collection are PAI Teachers, other teachers are also students of class V. With this method of documentation the author tries to collect data from documents related to media utilization in increasing the mastery of Islamic Religious Education (PAI) Negeri Lambaro Angan Aceh Besar. After the authors conduct research using some of the above methods, the authors can conclude that the use of media learning well will facilitate students to learn and more quickly learning materials.